Penggunaan alat pelindung diri (APD) terhadap pencegahan kecelakaan kerja. Studi kasus perilaku pada pekerja lapangan PT. PLN Unit Lueng Bata, Banda Aceh - Nasrullah Nasrullah (Jurnal SAGO Gizi dan Kesehatan, 2022)
Background: Applying work safety in a company is part of improving public health. Everyone who works is obliged to apply a safety pattern. Therefore, workers' knowledge in companies is fundamental to pay attention to, impacting safety and health during work.Objective: This study aims to determine the relationship between using personal protective equipment (PPE) and the prevention of work accidents in PT. PLN field workers in the Lueng Bata branch of Banda Aceh City.Method: This analytical descriptive study used a cross-sectional design. Research has been conducted at PT. PLN (Persero) ULPLTD Lueng Bata branch, Banda Aceh City, in 2019. The sample has been taken using a total population of 50 workers. Data collection of knowledge, attitudes, and actions has been carried out by direct interviews using questionnaires. Processing through the stages of inspection, coding, filing, and processing. The analysis used Chi-Square statistical test at 95% CI.Results: The results showed that there was a significant relationship between knowledge (p= 0.013; OR= 6.7), attitude (p= 0.006; OR= 12.2), and action (p= 0.000; OR= 21.4) in the use of personal protective equipment (PPE) in the prevention of work accidents at PT. PLN Lueng Bata branch, Banda Aceh City.Conclusion: The behavior (knowledge, attitudes, and actions) in using personal protective equipment (PPE) influences the prevention of work accidents.